2009
DOI: 10.1007/s00122-009-1145-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci for resistance to shoot fly in sorghum [Sorghum bicolor (L.) Moench]

Abstract: The shoot fly is one of the most destructive insect pests of sorghum at the seedling stage. Deployment of cultivars with improved shoot fly resistance would be facilitated by the use of molecular markers linked to QTL. The objective of this study was to dissect the genetic basis of resistance into QTL, using replicated phenotypic data sets obtained from four test environments, and a 162 microsatellite marker-based linkage map constructed using 168 RILs of the cross 296B (susceptible) x IS18551 (resistant). Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 62 publications
6
67
1
Order By: Relevance
“…The need for having shoot fly resistance in both female and male parents for producing shoot fly resistant high yielding hybrids was demonstrated [27]. In sorghum, quantitative trait loci (QTL) governing various component traits contributing for shoot fly resistance have been identified and mapped in the parent IS 18551 [28] and CT Hash, ICRISAT, Personal communication). The QTL have been transferred to two cultivated backgrounds namely, BTx623 and 296B at ICRISAT (Hash CT, ICRISAT, Personal communication).…”
Section: Shoot Fly Resistancementioning
confidence: 99%
“…The need for having shoot fly resistance in both female and male parents for producing shoot fly resistant high yielding hybrids was demonstrated [27]. In sorghum, quantitative trait loci (QTL) governing various component traits contributing for shoot fly resistance have been identified and mapped in the parent IS 18551 [28] and CT Hash, ICRISAT, Personal communication). The QTL have been transferred to two cultivated backgrounds namely, BTx623 and 296B at ICRISAT (Hash CT, ICRISAT, Personal communication).…”
Section: Shoot Fly Resistancementioning
confidence: 99%
“…Consequently, pests and pathogens of reproductive growth are much less important. If grain is important, then breeding for resistance to midge and shoot fly are important because these pests reduce grain yield [100][101][102][103].…”
Section: Breeding For Stress Tolerancementioning
confidence: 99%
“…Several studies have implied that pesticides and other agricultural chemicals can affect the epicuticular lipid composition, reducing the ability of the crop to resist insect attack [92,93]. To date, multiple genes have been identified for the gloss leaf trait in cabbage, and 18 loci have been mapped using mutants of maize and sorghum [88,94,95]. Although leaf waxes can vary with crop age and be influenced by the production environment, they provide an avenue for breeders to develop varieties that are suited for specific agroecosystems while improving pest resistance, yield loss, and overall sustainability of low-input systems.…”
Section: Energy and Pesticidesmentioning
confidence: 99%
“…In addition, trichome morphology has also been shown to play an important role in limiting pest establishment within a crop. Sorghum genotypes with unicellular pointed trichomes were less susceptible to insect damage than genotypes possessing bicellular blunt trichomes [94]. Satish et al [94] identified eight QTLs (quantitative trait loci) for trichome density using sorghum, two of which were specific for upper leaf surface, the remaining six specific to the lower leaf surface.…”
Section: Energy and Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation